al-Wujūd al-ʻUthmānī fī Miṣr fī al-qarnayn al-sādis ʻashar wa-al-sābiʻ ʻashar : dirāsah wathāʼiqīyah - Muḥammad, ʻIrāqī Yūsuf, (Markaz Kliyūbātrā lil-Kumbiyūtar, 1996)
Ottomans in Egypt from the 16th-17th century. Study based on archives.